Caracterización cualitativa del zooplancton del Área de Conservación Marina Isla del Coco (ACMIC), Océano Pacífico de Costa Rica - Morales-Ramírez, Álvaro (Revista de Biología Tropical, 2008)
Qualitative characterization of the zooplankton of the Cocos Island Marine Conservation Area (Área de Conservación Marina Isla del Coco, ACMIC), Pacific Ocean of Costa Rica. During November 2001, zooplankton samples were obtained from sites around Isla del Coco, a protected oceanic island off the Pacific coast of Costa Rica. Vertical (0-50 m) and horizontal hauls were performed. This first qualitative analysis of the zooplankton shows a very diverse community, with copepods being dominant (68 species). Up to 19 species of Copepoda represent new records for Costa Rican Pacific waters and thus, increase the relative number of species recorded from Costa Rica in relation to the overall copepod species richness of the eastern tropical Pacific. Hyperiid amphipods were represented by 20 species; this is the first reference about this group from waters around Isla del Coco. Other planktic crustaceans recorded were Evadne sp. (Cladocera), Cypridina americana and Euconchoecia sp. (Ostracoda), and unidentified euphausiids and mysidaceans. Six families of planktic gastropods were found, including Limacinidae, Cavolinidae, Pneumodermopsidae, and Desmopteridae; heteropod molluscs were also collected (Pterotracheidae, Carinariidae and Atlantidae), and also the nudibranch Phylliroë bucephala (Phylliroidae). Seven species of chaetognaths were recorded, Flaccisagitta enflata and Serratosagitta pacifica being the commonest. Appendicularians (five species of Oikopleura and Stegosoma) and salps (Salpa sp. and Doliolum sp.) were also present in the samples. Pyrosomatida (Thaliacea) are first records for Costa Rican Pacific waters. The gelatinous zooplankton included seven species of siphonophores and three of medusae, Rhopalonema velatum being the most frequent medusa. Overall zooplankton species diversity (including ichthyoplankton) of Isla del Coco is lower, but not by much, than in the Costa Rica Dome (136 vs 178). Some ideas are discussed about the value of Isla del Coco as a zooplankton diversity hot spot. Rev. Biol. Trop. 56 (Suppl. 2): 159-169. Epub 2008 August 29.